Persistent lipoprotein(a) exposure and its association with clinical outcomes after acute myocardial infarction: a longitudinal cohort study - Zhenwei Wang; Junnan Tang; Qian Shi; Lijuan Fang; Naifeng Liu; Jinying Zhang (Annals of Medicine)
Aims To assess the link between persistent lipoprotein(a) [Lp(a)] exposure levels and clinical outcomes in patients with acute myocardial infarction (AMI).Methods This longitudinal cohort study included 1131 AMI patients, categorizing persistent Lp(a) exposure based on measurements at admission and after 1 year. Patients were segmented into four groups using a 300 mg/L Lp(a) threshold: (1) persistent low Lp(a) (lowon admission – lowat 1 year); (2) fortified Lp(a) (lowon admission – highat 1 year); (3) attenuated Lp(a) (highon admission – lowat 1 year); and (4) persistent high Lp(a) (highon admission – highat 1 year). Multivariate Cox regression, subgroup analysis and sensitivity analysis assessed the association between Lp(a) trajectories and major adverse cardiovascular and cerebrovascular events (MACCE), cardiovascular death, non-fatal MI, non-fatal stroke, unplanned revascularization, and all-cause death.Results Over a median 50-month follow-up, 343 (35.70%) patients encountered MACCE, and 210 (18.70%) died, including 126 (11.20%) from cardiovascular causes. The group with persistent high Lp(a) faced increased risk of MACCE (HRadjusted, 1.871; 95% CI: 1.474–2.374), non-fatal stroke (HRadjusted, 1.647; 95% CI: 1.031–2.632), unplanned revascularization (HRadjusted, 1.571; 95% CI: 1.008–2.449), and both all-cause (HRadjusted, 1.546; 95% CI: 1.134–2.108) and cardiovascular death (HRadjusted, 2.163; 95% CI: 1.405–3.331), compared to the persistent low Lp(a) group.Conclusions In AMI patients, sustained high Lp(a) levels were significantly associated with increased risk of MACCE, non-fatal stroke, unplanned revascularization, and both all-cause and cardiovascular death.